2019
DOI: 10.1093/ehjci/jez157
|View full text |Cite
|
Sign up to set email alerts
|

Normal left atrial strain and strain rate using cardiac magnetic resonance feature tracking in healthy volunteers

Abstract: Aims The aim of our study was to establish normal ranges for left atrial (LA) strain and strain rate using cardiac magnetic resonance feature tracking (CMR-FT), LA sphericity index, and to compare LA strain using CMR-FT with 2D-speckle tracking echocardiography (STE) in a healthy population. Methods and results A total of 112 volunteers (45 male, 67 female) had adequate tracking for analysis on CMR-FT (Circle Cardiovascular I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 22 publications
17
90
0
Order By: Relevance
“…The absolute values of LA strain reported in this study were lower than those reported elsewhere [ 36 ], though comparable with some studies using CMR myocardial feature tracking. Values from healthy, yet elderly controls in studies by Evin et al [ 37 ] and Lamy et al [ 38 ] matched our relatively old and obese control group closely [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…The absolute values of LA strain reported in this study were lower than those reported elsewhere [ 36 ], though comparable with some studies using CMR myocardial feature tracking. Values from healthy, yet elderly controls in studies by Evin et al [ 37 ] and Lamy et al [ 38 ] matched our relatively old and obese control group closely [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Most studies assessing reproducibility of an imaging technique focus on inter-and intra-observer variability [32][33][34]. However, whilst important, observer variability does not address the multiple potential sources of variability when assessing the LA function, including image planning and acquisition, inclusion or exclusion of pulmonary veins/LA appendage from the LA volume as well as day-to-day physiological variation and filling status of the subject.…”
Section: Test-retest Reproducibilitymentioning
confidence: 99%
“…Quantification of RV and atrial deformation is challenging due to thin-walled anatomy, complex geometry and single plane analyses especially of the right heart, but CMR imaging has been shown to offer great potential for accurate assessment of these cardiac compartments [15]. Consequently, both RV [29,30] and atrial [28,31,32] deformation analyses are coming to the fore in current CMR-FT-based research, proving feasibility, generating reference values, demonstrating reproducibility and utilizing RV as well as atrial CMR-FT parameters in various cardiac diseases. In detail, similar to LV GLS analyses RV longitudinal strain evaluations can be derived from 4-chamber long-axis views.…”
Section: Deformation Quantification Beyond LVmentioning
confidence: 99%